Effects of adenylates on the circadian interaction of KaiB with the KaiC complex in the reconstituted cyanobacterial Kai protein oscillator. Issue 11 (2nd November 2014) - Goda, Kazuhito; Kondo, Takao; Oyama, Tokitaka
Abstract: Cyanobacteria are photosynthetic prokaryotes that possess circadian oscillators. Clock proteins, KaiA, KaiB, KaiC compose the central circadian oscillator, which can be reconstituted in vitro in the presence of ATP. KaiC has ATPase, autokinase, and autophosphatase enzymatic activities. These activities are modulated by protein–protein interactions among the Kai proteins. The interaction of KaiB with the KaiC complex shows a circadian rhythm in the reconstituted system. We previously developed a quantitative, real-time monitoring system for the dynamic behavior of the complex using fluorescence correlation spectroscopy. Here, we examined the effects of ATP and ADP on the rhythmic interaction of KaiB. We show that increased concentration of ATP or ADP shortened period length. Adding ADP to the Kai protein oscillation shifted its phase in a phase-dependent manner. These results provide insight into how circadian oscillation entrainment mechanism is linked to cellular metabolism. Graphical abstract: : Increased concentration of ATP or ADP shortened the period length of the rhythmic interaction between KaiB and the KaiC complex.